Profound Hypoglycemia and High Anion Gap Metabolic Acidosis in a Pediatric Leukemic Patient Receiving 6-Mercaptopurine - Molly O'Shea; Alexis Kuhn; Ana L. Creo; Mira Kohorst; Asmaa Ferdjallah (MDPI AG, 2024)
A 13-year-old male undergoing maintenance chemotherapy with methotrexate and 6-mercaptopurine (6MP), for very high-risk B-cell acute lymphoblastic leukemia (ALL), presented with vomiting due to severe hypoglycemia with metabolic acidosis. While his laboratory values were concerning for a critically ill child, the patient was relatively well appearing. Hypoglycemia is a rare but serious side effect of 6MP with an unexpectedly variable presentation; therefore, a high index of suspicion is needed for its prompt detection and treatment. This patient also had severe metabolic acidosis, likely secondary to hypoglycemia, creating a serious clinical picture despite a well-appearing child. This example of incongruity between laboratory tests and clinical appearance adds nuance to the existing literature. Moreover, although 6MP-associated hypoglycemia is rare, it may be more prevalent than the literature suggests, as symptoms of hypoglycemia-nausea, vomiting, and somnolence-mirror common chemotherapy side effects. 6MP-induced hypoglycemia can be ameliorated with the addition of allopurinol to shunt metabolism in favor of the production of therapeutic metabolites over hepatotoxic metabolites. Additionally, a morning administration of 6MP and frequent snacks may also help to prevent hypoglycemia. Overall, this case adds to the literature of unusual reactions to 6MP including hypoglycemia in an older child without traditional risk factors.